The Secret Life of Salona in 7th and 8th Century - Džino, Danijel (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
This paper analyses the available evidence for habitation of the ancient Dalmatian capital Salona during the seventh and eighth centuries. The existing scholarship, with few exceptions, accepts that Salona was taken by the Slavs and Avars before mid-seventh century, probably within the decades of 620s or 630s. However, the lack of archaeological evidence proving the destruction of the city creates space for arguments that the city did not meet a violent end, but rather that it slowly died out, as argued in the works of Rapanić, Goldstein, Budak and the present author. The paper argues that Salona did not meet a violent end in seventh century, but that some kind of habitation existed until eighth century. One plausible possibility could be that some traumatic event happened in eighth century, ending continuity of life within the city-walls.